The Effects Of Health Promotion Through Animation Video In Reducing Anxiety Among Hypertension Patients: A Literature Review - Haryoko, Imam; Rashid, Norhashima Abd; Tan, Chun Hoe (International Journal of Health Sciences, 2023)
Introduction: Anxiety is a state of unease or apprehension that arises from the expectation of potential harm, frequently without a clear or identifiable cause. An individual undergoing anxiety might induce a rise in blood pressure. Anxiety exacerbates hypertension by causing vasoconstriction, resulting in elevated blood pressure. Regarding the correlation between anxiety and hypertension, it is crucial to address anxiety in individuals with hypertension. There are multiple methods available to address this anxiety, including both pharmaceutical and non-pharmacological approaches. Material and Methods: This study is a review of existing literature. The researchers aimed to locate scholarly literature about the use of animated movies as a means of alleviating anxiety in individuals diagnosed with hypertension. Articles about the specified theme were chosen from 2018 to 2023 using electronic databases such as Science Direct, PubMed, and Google Scholar and open knowledge maps during the article search. The researchers employed the PRISMA methodology to analyze the literature review studies. Results: 174 articles were chosen using the keywords Health Promotion, Animation Video, Anxiety, and Hypertension. The research underwent a comprehensive review encompassing its aims, samples, methods, and results. Based on the literature review findings, there needs to be more participants or samples that align with the focus of this study. Researchers did not discover any instances of anxiousness in individuals with hypertension through the examination of samples. However, researchers conducted studies on various topics, including the impact of using animated videos to promote health in reducing anxiety among postpartum patients, preoperative anxiety in children, and hypertension. These findings are presented in Table 1. Nevertheless, scholars might engage in discussions regarding the impacts of animated videos. The researchers selected and evaluated only ten publications despite their lack of relevance to the research area of this literature review. Conclusion: Out of the 10 articles examined, many employed animated videos as interventions. However, researchers did not discover any studies specifically focused on investigating the impact of using animated videos for health promotion in reducing anxiety among hypertensive patients. The researchers discovered an independent subject. Consequently, researching this topic can contribute innovatively to future investigations.